PENGARUH WORK STRESS DAN BURNOUT TERHADAP TURNOVER INTENTION KARYAWAN - Wegi Anggero Pratama; Sri Ekowati (UM. Bengkulu, 2026)
This research is motivated by the fact that studies on the influence of Work Stress and Burnout on Turnover intention in PT (GSB) have not been widely conducted, so it is important to explore the relationship between these three variables. By understanding the factors that cause turnover intention, companies can create a healthier and more conducive work environment, as well as increase employee loyalty. This research is expected to contribute to PT (GSB) in developing more effective human resource policies to overcome work stress and burnout, as well as reduce the level of turnover intention in the company. The importance of understanding the relationship between work stress, burnout, and employees' intention to leave the company, especially in the context of organizations that operate in certain regions with unique work dynamics. By studying these factors, the research is expected to provide input for PT GSB's management in designing a more effective HR management strategy, creating a supportive work environment and reducing the level of turnover intention. The purpose of this study was to determine work stress on employee turnover intention, the effect of burnout on employee turnover intention, and the effect of work stress and burnout on employee turnover intention at PT Galempa Sejahtera Bersama (GSB) Empat Lawang. The type of research used is quantitative research using a descriptive approach. The subjects in this study are employees of PT Galempa Sejahtera Bersama (GSB) Empat Lawang. The data collection techniques used are observation, documentation and questionnaires. Meanwhile, data analysis uses descriptive analysis, inferential analysis uses SPSS and determination coefficient analysis (R2). The results of this study show that Work stress has a positive effect on employee turnover intention at PT. Galempa Sejahtera Bersama (GSB) Four Lawang. This means that the higher the work stress, the higher the turnoven intention rate. Burnout has a positive effect on employee turnover intention at PT Galempa Sejahtera Bersama (GSB) Empat Lawang. This indicates that the higher the burnout, the higher the employee turnover intention. Work stress and burnout simultaneously or together have a positive and significant effect on employee turnover intention at PT. Galempa Sejahtera Bersama (GSB) Four Lawang. This means that if employees experience high stress and fatigue, it will affect the company Kata Kunci: Work stress, turnoven intention, burnout